Design of a Miniature Jumping Robot - Yunqian Ma; Deyi Kong (Jixie chuandong)
Aiming at problems that it's difficult for existing robots to move in complex unstructured environment such as forest，mountain and collapse area， a jumping robot which can carry reconnaissance or rescue equipment to move efficiently in the rugged environment is designed and developed. The total mass of the robot is 97.1 g and the maximum jump height is 1.5 m， it has certain load capacity，and thus it can carry equipment for practical application. First of all，the theoretical analysis and comparison of several design schemes of spring mechanism are carried out，and then the scheme with the best stability and the highest energy utilization rate is designed. Secondly，to enable the jumping mechanism to release energy instantaneously，a compact and reliable energy control mechanism is designed. The mechanism can effectively control the energy storage mechanism for fast energy storage and instantaneous release，so that the stored elastic potential energy can be efficiently converted into the kinetic energy of the robot. Finally，in terms of system integration of the robot，a theoretical analysis is conducted from two aspects and a reasonable overall mass distribution of the robot is obtained.